2023
DOI: 10.1111/jan.15589
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patterns of lifestyle behaviours linked to sociodemographic characteristics and health conditions among young adults in South Korea

Abstract: Aims:To identify specific patterns of lifestyle behaviours among young adults and examine the relationships of the patterns to sociodemographic characteristics and health conditions (hypertension, diabetes and obesity).Design: Descriptive, correlational study. Methods: Data from a nationally representative sample of 4562 young adults aged 19-39, who participated in the 2016-2018 Korea National Health and Nutrition Examination Survey, were analysed. Latent class analysis was used to identify the patterns of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Furthermore, studies have shown that unhealthy lifestyle patterns are associated with sociodemographic characteristics and health conditions [10][11][12]. Previous research has indicated that certain behavioral risk factors are more prevalent in women, while others are more common in men; moreover, these gender differences often vary with age [13].…”
Section: E P U Bmentioning
confidence: 99%
“…Furthermore, studies have shown that unhealthy lifestyle patterns are associated with sociodemographic characteristics and health conditions [10][11][12]. Previous research has indicated that certain behavioral risk factors are more prevalent in women, while others are more common in men; moreover, these gender differences often vary with age [13].…”
Section: E P U Bmentioning
confidence: 99%